استخدام التقنيات التحليلية المتقدمة في التخطيط الحضري الإمكانات والمعوقات - بركــــات طــارق (Latakia University Journal -Engineering Sciences Series, 2016)
تعد التقنيات الحديثة لنظم المعلومات إحدى أهم الأدوات التي تسعى المؤسسات والهيئات والمنظمات العاملة في مجالات التخطيط والتنمية المستقبلية إلى استخدامها بشكل أساسي كأدوات تحليلية وتقنية ذات فعالية في جمع وتحليل الكم الهائل من المعلومات والبيانات المكانية والوصفية للظواهر البشرية والطبيعية، سواء للمخططين أو أصحاب القرار، لمختلف مراحل العمليات التخطيطية، وبالتالي مواجهة المشاكل العمرانية العاجلة، إضافة إلى المساندة في إنجاز الخطط التنموية بزمن قياسي وجودة عالية، مع تقليل الهدر في الطاقات والموارد. في هذا السياق، يعرض البحث التقنيات والأدوات التحليلية المتقدمة ودورها في العمليات التخطيطية، والتعرف على أساليب تطبيق نظام المعلومات الجغرافية كأكثر النظم كفاءة واستخداماً في مجالات التخطيط الحضري واستعمالات الأراضي ودعم اتخاذ القرارات التنموية. كما يقدم البحث نموذجاً عملياً لتوزيع المهام ضمن أقسام ودوائر المؤسسات المعنية بالتخطيط من أجل إدخال نظم المعلومات في عملها، ويلقي الضوء على أهم المعوقات التي قد تواجه استخدام تلك النظم. ويخلص البحث إلى جملة من النتائج والتوصيات لإمكانيات تطبيق التقنيات المتقدمة وتفادي المعوقات، لتساهم بشكل مباشر في رفع كفاءة وفاعلية عمليات التخطيط الحضري، وتحسين مستوى إدارة العملية التخطيطية. The modern techniques of the information systems are considered as one of the most important tools, that most institutions, bodies and organizations working in the areas of planning and future development are seeking to use as effective analytical and technical tools for collecting and analyzing the vast amount of spatial and descriptive information and the data of the human and natural phenomena, for both planners or decision-makers, at the various stages of the planning process to cope with the urgent urban problems in addition to supporting the completion of development plans in record time and high quality, and reduce waste in energies and resources. In this context, the research displays the advanced analytical techniques and tool, and their role in whole planning processes, and identifies the methods of application of GIS systems as the most efficient and widely used system in the fields of urban planning and land use, and in developmental decisions support. Also, the research presents a practical model for the distribution of tasks within the departments and institutions involved in the planning, to introduce the information systems in their work, and highlights the most important obstacles that may face the use of those systems. The study comes up with a number of conclusions and recommendations for the potential application of advanced techniques and avoiding obstacles, which directly contribute to raising the efficiency and effectiveness of planning processes, and improving the planning process management.